Mid-career library and information professionals : a leadership primer - Lowe-Wincentsen, Dawn; Crook, Linda (Chandos information professional series., 2011)
More and more mid-career librarians are seeking leadership positions. This book offers advice on how to become a leader in library and information science from the middle of your career and achieve success in the workplace. In addition to tips and tools on leadership, you will find perspectives from others in the field who have advanced to leadership positions, and learn how to make your own career development plan.